When is evidence sufficient for decision-making? A framework for understanding the pace of evidence adoption. (July 2013) - Dubois, Robert W; Lauer, Michael; Perfetto, Eleanor
Translation of medical evidence into practice has not kept pace with the growth of medical technology and knowledge. We present three case studies – statins, drug eluting stents and bone marrow transplantation for breast cancer – to propose a framework for describing five factors that may influence the rate of adoption. The factors are: validity, reliability and maturity of the science available before widespread adoption; communication of the science; economic drivers; patients' and physicians' ability to apply published scientific findings to their specific clinical needs; and incorporation into practice guidelines.